Inovasi Packaging Keripik Ubi Resky menjadi keripik CIS untuk Mendukung Perekonomian Lokal - Supiati, Supiati; Bachtiar, Irmah Halimah; Gafur, Gafur; Nurmiati, Nurmiati; Rijal, Abdul Rahman Khaerul (STMIK Royal, 2024)
Representing a significant effort to support local economic growth which is an essential goal of the government. This project aimed to transform the packaging of Resky chips into chips in a glass (CIS), enhancing their competitiveness in the digital marketplace. Our partners faced several challenges, including limited knowledge of business management and marketing, insufficient production tools, and a lack of product innovation. The involvement of the community service team has provided renewed hope and guidance to these business owners. To tackle these issues, we utilized a combination of training and mentoring methods. Our training sessions covered key areas such as financial bookkeeping, production management, packaging innovation, marketing strategies, and product digitalization. As a result of these method, our partners have successfully adopted basic bookkeeping practices. The Resky chips have been rebranded with new packaging and labels, along with the introduction of a personal branding strategy for the CIS. They have also secured business license numbers (NIB) and distribution permits (PIRT), and we facilitated their application for a halal certificate. Resky’s Chips are now officially branded as CIS by Khasnah Food n Drink. Additionally, our partners have established a social media, with accounts on Instagram, a Facebook fan page, and a profile on Akkio Smart City, managed by the Gowa Regency Government.Keywords: Chips; CIS; MSMEs; product digitalization; packaging innovation Abstrak: Dukungan terhadap UMKM merupakan salah satu gebrakan pemerintah dalam meningkatkan perekonomian lokal. Tujuan dilakukannya PKM ini adalah untuk melakukan transformasi kemasan keripik ubi Resky menjadi keripik CIS (chips in a glass) agar dapat bersaing di dunia digital. Permasalahan utama yang dialami mitra adalah minimnya pengetahuan pemilik usaha dalam manajemen usaha, minimnya pengetahuan pemilik usaha dalam pemasaran, keterbatasan alat produksi dan inovasi produk belum dilakukan. Kehadiran pengusul PKM membawa harapan besar bagi mitra. Metode yang digunakan oleh pengusul yaitu pelatihan dan pendampingan. Pelatihan yang dilakukan meliputi pembukuan keuangan sederhana, managemen produksi, inovasi packaging, serta managemen pemasaran dan digitalisasi produk. Hasil kegiatan yang dilakukan menunjukkan bahwa mitra telah mampu membuat pembukuan sederhana, kemasan baru dari keripik ubi resky telah disertai dengan label, personal branding cips in a glass, nomor izin berusaha (NIB), dan izin edar berupa nomor Pangan Industri Rumah Tangga (PIRT). Pengusul juga telah melakukan pengajuan sertifikat halal untuk mitra. Saat ini keripik Ubi milik Ibu Resky telah berubah nama menjadi Keripik CIS by Khasnah Food n Drink. Mitra juga telah membuat media sosial berupa Instagram, fanpage facebook dan akun di Akkio Smart City milik Pemerintah Kabupaten Gowa.Kata Kunci: Keripik; CIS; UMKM; digitalisasi produk; inovasi kemasan